The effect of customer perceived value on customer satisfaction: a case study of Malay upscale restaurants - Mohd Nazri Abdul Raji,; Artinah Zainal, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Stiff competition and increasingly high operating costs have driven many international and domestic players to introduce new outlet concepts. Malay fine dining, upscale restaurant segment is gaining popularity among Malaysian, especially in Kuala Lumpur. This study examined the effect of perceived value on customer satisfaction in Malay upscale restaurants in terms of emotional responses, monetary prices, behavioral price and reputation. Primary data were gathered from 170 questionnaires returned by respondents from five Malay upscale restaurants in Kuala Lumpur, and statistically analysed using SPSS version 21. The findings of this study revealed that monetary prices had a high positive relationship with customer satisfaction. In addition, the beta value for emotional responses (β=0.530, p<0.01), behavioral price (β=0.180, p<0.01) and reputation (β=0.168, p<0.01) also indicated the respective contributions made to customer satisfaction.